Design and performance study of hydrophilic and super hydrophilic capillary valves for novel microfluidics systems / Amin Kazemzadeh - Amin, Kazemzadeh (2015)

(untitled)
The research in this PhD thesis is motivated by the importance of precise microflow control in transforming various laboratory-based chemical and clinical assays into portable centrifugal microfluidics based devices. The more specific aim is the development of inexpensive flow control and liquid routing techniques that can be used in sample preparative processes such as blood plasma separation, washing, metering, and analyte detection. Efficient and inexpensive flow control techniques based on new principles and operations are introduced and compared with state of the art industrial approaches. Unlike previously introduced techniques these novel flow control methods are not dependent on the direction of the disk rotation and do not require special surface treatments or external power sources. The hardware to enable these techniques is easy to implement and provides robust control of the flow in centrifugal microfluidic platforms. Prior to designing new capillary valves, a comprehensive investigation of the relationship between contact angles and capillary dimensions on the performance of passive capillary valves was carried out. The results reveal, for example, that square capillaries have lower capillary forces compared to rectangular capillaries. The results also show that -contrary to earlier theoretical predictions- the capillary force at burst valves dramatically drops when the contact angle decreases. For the first time, a new valving technique is introduced that exploits a geometrical effect on the surface tension to control and switch the flow direction. The valve is a frequency dependent device that is able to direct the flow to one direction (e.g., c.w.) at low frequencies and to the opposite direction (e.g., c.c.w.) at higher frequencies without using external power sources or applying surface treatments. The flow behavior of the new valve for distilled water as well as for liquids with different properties was investigated experimentally and numerically. The results show that the new valve is v able to control the flow direction on a spinning microfluidic platform for liquids of widely varying properties. Another novel microvalve is presented that allows for the efficient routing of samples, switching and controlling the flow direction on centrifugal microfluidic platforms. The distinctive feature that makes this approach different from other types of passive capillary valves is the robust control of liquid movement, which is achieved by employing two adjustable sequential burst valves i.e., a primary and a secondary burst valve. The performance of this novel configuration was experimentally tested, the flow behavior was numerically studied using the VOF method and a theoretical model for their burst frequency was presented. For the first time, the role of the effective moment of inertia of the liquid in centrifugal microfluidics – that can be used for pushing the liquid towards specific lateral or/and radial directions – was theoretically, experimentally and numerically investigated. The experiment results confirmed that utilizing the effective moment of inertia of the liquid i.e., as a result of a sudden reduction of the rotational speed (~45 Hz/s), propels the entire liquid volume from a chamber adjacent to the disc’s periphery to a chamber close to the disc center.